2016
DOI: 10.1016/j.conctc.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Methods to reduce medication errors in a clinical trial of an investigational parenteral medication

Abstract: There are few evidence-based guidelines to inform optimal design of complex clinical trials, such as those assessing the safety and efficacy of intravenous drugs administered daily with infusion times over many hours per day and treatment durations that may span years. This study is a retrospective review of inpatient administration deviation reports for an investigational drug that is administered daily with infusion times of 8-24 hours, and variable treatment durations for each patient. We report study desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…A more stringent standard of error rates, close to zero, is needed. 20 The overall prescribing error rate in this study was 5.36%, which was higher than that in general anticancer drug studies. Prescribing error rates in general anticancer studies were reported to be 1.1-3%.…”
Section: Discussioncontrasting
confidence: 58%
“…A more stringent standard of error rates, close to zero, is needed. 20 The overall prescribing error rate in this study was 5.36%, which was higher than that in general anticancer drug studies. Prescribing error rates in general anticancer studies were reported to be 1.1-3%.…”
Section: Discussioncontrasting
confidence: 58%
“…The systematic search on Medline (Ovid) found 47 articles describing systemic defenses to prevent IV MEs published between June 2016 and October 2021 (Supplementary file 3, http://links.lww.com/JPS/A612). The studies were conducted in the United States (n = 16), 47–62 the United Kingdom (n = 7), 63–69 Australia (n = 3), 70–72 Brazil (n = 3), 73–75 Spain (n = 3), 76–78 Mexico (n = 2), 79,80 Saudi Arabia (n = 2), 81,82 Singapore (n = 2), 83,84 Canada (n = 1), 85 China (n = 1), 86 France (n = 1), 87 Germany (n = 1), 88 Italy (n = 1), 89 Netherlands (n = 1), 90 and Switzerland (n = 1) 91 . Some studies (n = 2) were carried out in multiple countries 92,93 .…”
Section: Resultsmentioning
confidence: 99%
“…lww.com/JPS/A612). The studies were conducted in the United States (n = 16), [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] the United Kingdom (n = 7), [63][64][65][66][67][68][69] Australia (n = 3), [70][71][72] Brazil (n = 3), [73][74][75] Spain (n = 3), [76][77][78] Mexico (n = 2), 79,80 Saudi Arabia (n = 2), 81,82 Singapore (n = 2), 83,84 Canada (n = 1), 85 China (n = 1), 86 France (n = 1), 87 Germany (n = 1), 88 Italy (n = 1), 89 Netherlands (n = 1), 90 and Switzerland FIGURE 2. Outline of the narrative review process, analysis of the included articles (n = 63), and comparison to our previous systematic reviews.…”
Section: Description Of Studies Exploring Systemic Defenses To Preven...mentioning
confidence: 99%
See 2 more Smart Citations